Aglutininas anti-Brucella abortus no soro e em secreção de bursite cervical em eqüinos - Ribeiro M.G.; Nardi Júnior G.; Megid J.; Paes A.C.; Listoni F.J.P. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2003)
Fistulous wither secretions from three horses were tested by the plate agglutination (PAT), tube agglutination (SAT), buffered plate-Rose Bengal (RBPT) and 2-mercaptoethanol (2-ME) tests, comparatively with standard agglutination tests. In the modified tests, titers were increased in the PAT, SAT and 2-ME tests and positive reaction was observed in RBPT. Brucella abortus was isolated from the secretion of fistulous withers collected from one animal. These results suggest that the modified tests may be used as alternative tests to diagnose brucellosis in horses with fistulous withers.